Influence of geometric and material nonlinearities on the behaviour and design of stainless steel frames. (December 2021) - Walport, F.; Arrayago, I.; Gardner, L.; Nethercot, D.A.
Abstract: Material nonlinearity affects the stiffness and consequently the distribution of internal forces and moments in indeterminate structures. This has a direct impact on their behaviour and design, particularly in the case of stainless steel, where material nonlinearity initiates at relatively low stress levels. A method for accounting for the influence of material nonlinearity in stainless steel frames, including making due allowance for the resulting amplified second order effects, is presented herein. Proposals have been developed for austenitic, duplex and ferritic stainless steels. The method was derived based on benchmark results calculated through second order inelastic analysis with strain limits, defined by the Continuous Strength Method, using beam finite element models. A comprehensive set of frames was modelled and the proposed assessment of second order effects in the plastic regime was also verified against the results of four full-scale stainless steel frame tests. The proposed method is due to be included in the upcoming revision to Eurocode 3 Part 1.4 Graphical abstract: Unlabelled Image Highlights: Review of current provisions for global analysis of stainless steel structures; Benchmark results generated for a series of stainless steel frames using GMNIA; Limit proposed for when plastic zone analysis is needed for stainless steel design; New method proposed for treatment of second order effects in plastic regime; Proposals verified against extensive FE results and four frame test results.